Análisis del discurso oral de jóvenes pertenecientes a las parroquias cacha y Flores del cantón Riobamba - Janeta Quisay, Jessica Maribel (2025)
The study entitled “Analysis of the Oral Discourse of Young People from the Cacha and Flores Parishes in the Riobamba Canton” represents a crucial investigation for understanding communicative dynamics in rural contexts. The central objective of this research is to determine the presence of Kichwa in the everyday speech of young people, to examine the extent to which social changes and cultural traditions influence their discursive practices, and to analyze patterns of linguistic variation based on their educational level and sociocultural context. This qualitative study employed a non-experimental design, which allowed for data collection without the manipulation of variables, thereby enabling an in-depth understanding of the observed reality. For this purpose, two rural parishes—Cacha and Flores—were selected, locations where no prior linguistic studies have been conducted, thus permitting an exploration of linguistic and cultural interactions relevant to the topic of this research. The applied methodology facilitated direct and meaningful interaction with six young participants from the aforementioned localities, whose expressions and experiences served as the primary focus of this research. The main technique used was the interview, accompanied by a series of semi-structured questions designed to collect key texts that subsequently served as the basis for the analyses. These records made it possible to uncover the participants’ perceptions and the linguistic uses most common among these youths. Finally, the findings revealed that most participants prefer to use Spanish in their everyday conversations. These results demonstrate the profound impact that social changes have on their culture and, consequently, on their language. The tendency toward Spanish as the primary language is reinforced by globalization and digital media, as well as by the need to integrate into broader social spheres. However, one of the noteworthy points of the study was the awareness shown by certain young participants regarding this issue, as some of them independently seek to revitalize, promote, and reinvigorate their cultural identity and the use of Kichwa in various contexts and cultural spaces. This highlights that, despite changes in lifestyles, a portion of the youth continue to make efforts to preserve and reclaim the linguistic and cultural essence of their community